Hubungan Pengetahuan Ibu tentang Imunisasi Dasar terhadap Kepatuhan Pemberian Imunisasi Dasar Pada Bayi di Puskesmas Jatiasih Tahun 2025 - Sarah May Vauli Rambe; Omega DR Tahun (Jurnal Ners, 2025)
Immunization is one of the efforts to improve child health through the prevention of infectious diseases in an effective and efficient way. In Indonesia, the basic immunization program is provided to infants to protect them from diseases that can cause high morbidity and mortality, such as diphtheria, tetanus, and hepatitis B. Although the government has promoted the immunization program, parental compliance, especially mothers, in providing basic immunization to infants remains a challenge. In Jatiasih Health Center in 2025, not all immunizations for infants have reached the target coverage, which is suspected to be related to the mother's knowledge of basic immunization. This study aims to determine whether there is a relationship between the mother's knowledge of basic immunization and compliance in administering basic immunization to infants at the Jatiasih Health Center. This research uses an observational analytic method with a cross-sectional approach and simple random sampling technique. The respondents in this study were 100 mothers who had their infants immunized at the Jatiasih Health Center in 2025. The measurement of the mother's knowledge about basic immunization was done using a questionnaire, and the measurement of compliance in administering basic immunization was done using the KMS book. The data analysis technique used was the Chi Square test. The results of the Chi Square test were used to determine the relationship between the mother's knowledge of basic immunization and her compliance in administering immunization. The analysis results obtained a p-value of 0.013 (P < 0.05), indicating a relationship between the mother's knowledge of basic immunization and her compliance in administering basic immunization to infants at the Jatiasih Health Center. It can be concluded that there is a relationship between the mother's knowledge of basic immunization and compliance in administering basic immunization to infants at the Jatiasih Health Center, where better knowledge about basic immunization encourages mothers to comply with immunization administration.